The Influence of Heel Height on Strain Variation of Plantar Fascia During High Heel Shoes Walking-Combined Musculoskeletal Modeling and Finite Element Analysis - Wang, Meizi; Li, Shudong; Teo, Ee-Chon; Fekete, Gusztáv; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2021)
The therapeutic benefit of high heel shoes (HHS) for plantar fasciitis treatment is controversial. Even with increased strain value on plantar fascia with heel elevation, the repetitive tension caused by HH wearing resulting in plantar fasciitis is a high-risk disease in HHS individuals who suffer heel and plantar pain. To explore the biomechanical function on plantar fascia under HHS conditions, in this study, musculoskeletal modeling (MsM) and finite element method (FEM) were used to investigate the effect of heel height on strain distribution of plantar fascia. Three-dimensional (3D) and one-dimensional (1D) finite element models of plantar fascia were generated to analyze the computed strain variation in 3, 5 and 7 cm of heel heights. For validation, the computed foot contact pressure was compared with experimental measurement, and strain value on 1D fascia was compared with previous studies. Results showed that the peak strain of plantar fascia was progressively increased on both 3D and 1D plantar fascia as heel elevated from 3cm to 7cm, and the maximum strain of plantar fascia occurs near the heel pain site at second peak stance. 3D fascia model predicted higher strain magnitude than that of 1D, and provided a more reliable strain distribution on plantar fascia. It is concluded that HHS with narrow heel support could pose a high risk on plantar fasciitis development, rather than reducing symptoms. Therefore, the heel elevation as a treatment recommendation for plantar fasciitis is questionable. Further studies of different heel support structures of shoes to quantify the effectiveness of heel elevation on the load-bearing mechanism of plantar fascia recommended.